Sistem Informasi Pemesanan Semen Curah Pada PT.Sumber Niaga Interindo Berbasis Webgis - Suryani, Ade Irma; Rahmelina, Liranti; Maulidi, Syahri (UIN Imam Bonjol Padang, 2021)
The purpose of building an information system for Bulk Cement Ordering at PT Sumber Niaga Interindo is to facilitate bulk cement ordering, provide reports that can be stored in the information system with a database and the driver will be assisted in locating locations with the Map feature. The problem that the authors found was that ordering bulk cement was still done manually, such as by telephone, sms and via other social media, reports that were not compiled, and the difficulty of the driver in finding a new ordering location or had never been visited by the driver. For data collection methods carried out is by conducting interviews and literature studies, and the software development method used is the SDLC (System Development Life Cycle) method, namely warterfall, while the tools used in designing this application are unified modeling language and this application was built using web-based PHP programming language. The final result of this research is the creation of Bulk Cement Ordering Information System at PT. Sumber Niaga Interindo based on Webgis which can speed up or simplify the process of ordering bulk cement, reports that are automatically generated by the system after placing the order and overcoming the difficulty of the driver in finding the location of the order.Â